1986
DOI: 10.2307/3576549
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein Levels Are Not Elevated in Heat-Resistant B16 Melanoma Cells

Abstract: Heat-resistant variants have been selected from B16 melanoma cells and from surface mutants previously derived from them. The aim of the present study was to explore the possible role of heat shock proteins in the manifestation of this heat resistance. The major heat shock proteins evident after heating have subunit molecular weights of 68, 70, 89, and 110K on sodium dodecyl sulfate-polyacrylamide gels. The 68-kDa protein is not evident in any of the unheated B16 cell lines while the levels of the other heat s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 14 publications
2
14
0
1
Order By: Relevance
“…In some cases, it was reported that the CHX effect on TT expression depended on the test temperature used Dewey, 1987a, 1988). Furthermore, some heat-resistant variants showed elevated HSP levels (Laszlo and Li, 1985;Chretien and Landry, 1988;Landry et al, 1989;Li and Mak, 1989) while others did not (Anderson et al, 1986). Finally, slow rates of heating can cause substantial thermotolerance, with greatly reduced or no detectable HSP synthesis (Tomasovic et al, 1983;Anderson et al, 1988).…”
mentioning
confidence: 99%
“…In some cases, it was reported that the CHX effect on TT expression depended on the test temperature used Dewey, 1987a, 1988). Furthermore, some heat-resistant variants showed elevated HSP levels (Laszlo and Li, 1985;Chretien and Landry, 1988;Landry et al, 1989;Li and Mak, 1989) while others did not (Anderson et al, 1986). Finally, slow rates of heating can cause substantial thermotolerance, with greatly reduced or no detectable HSP synthesis (Tomasovic et al, 1983;Anderson et al, 1988).…”
mentioning
confidence: 99%
“…Remarkably, whereas heat and BA priming exerted similar protective effects, BA treatment evoked weaker HSP response relative to heat priming at a HSP level. Noteworthy, no major differences were found in the levels of major HSPs between the heat sensitive B16 parent line and the heat resistant variants in other work, suggesting that HSPs are not a determining factor in the heatresistant phenotype of B16 melanoma cells [76]. Thus, the acquired heat tolerance observed in this study should involve other mechanisms (see above) rather than solely the de novo synthesis of HSP chaperones.…”
Section: Acquisition Of Thermotolerance Via Prior Membrane Hyperfluidmentioning
confidence: 61%
“…Segundo SCHMIDT-NIELSEN (1983) três variáveis podem atuar: 1) as condições de temperatura ambiente em que o animal estava habituado antes da exposição ao calor; 2) as condições gerais do organismo, tais como a quantidade de lí- LINDQUIST & GRAIG (1988) a tolerância térmica é um efeito temporário contra temperaturas letais, induzida por proteínas em células e organismos após um condicionamento térmico a temperaturas intermediárias ou depois do stress provocado principalmente por tratamento com calor. ANDERSON (1986), seguindo a mesma linha experimental, observou células com diferentes níveis de tolerância ao calor, mas sem alteração da síntese de proteínas de resistência a altas temperaturas. ARTMOWIDJOJO et al (1997) estudaram a tolerância a altas temperaturas no deserto do Arizona em A. mellifera e chegaram a um limite de 57ºC atingindo um limite de sobrevivência bem mais elevado do que S. postica que suportou no seu limite extremo 41,5ºC no verão.…”
Section: Discussionunclassified